2018
DOI: 10.1051/sm/2018016
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise program, a strategy to prevent cardiotoxicity in early breast cancer: A literature review

Abstract: Breast cancer, the most common in women, is a cancer of good prognosis. During this last decade, the improvement of cancer screening and treatment has significantly increased disease-free and overall survival. However, the chemotherapy, especially based on anthracyclines, and targeted therapies like trastuzumab have a toxicity to the cardiovascular system. If physical exercise is recognized as beneficial in tertiary prevention, especially by reducing fatigue, improving the physiological capacities of exercise,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…[14][15][16][17] As such, there is growing interest in the ability of exercise to attenuate declines in GLS and LVEF and prevent CTRCD in patients undergoing cardiotoxic chemotherapy for the treatment of breast cancer. 18,19 As GLS is a highly sensitive measure that can detect early changes in myocardial function, and is recognized to precede reductions in LVEF, 5,10 frequent monitoring of GLS during AC chemotherapy may provide the greatest insight into the ability of exercise to prevent asymptomatic CTRCD. A systematic review performed by the current authors found the ability of exercise to prevent CTRCD was unclear due to the small number of studies and large diversity in methodology and interventions between studies in this field.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] As such, there is growing interest in the ability of exercise to attenuate declines in GLS and LVEF and prevent CTRCD in patients undergoing cardiotoxic chemotherapy for the treatment of breast cancer. 18,19 As GLS is a highly sensitive measure that can detect early changes in myocardial function, and is recognized to precede reductions in LVEF, 5,10 frequent monitoring of GLS during AC chemotherapy may provide the greatest insight into the ability of exercise to prevent asymptomatic CTRCD. A systematic review performed by the current authors found the ability of exercise to prevent CTRCD was unclear due to the small number of studies and large diversity in methodology and interventions between studies in this field.…”
Section: Introductionmentioning
confidence: 99%